New Perspectives in Health Promotion Health in All Policies (HiAP). - Amdam, Roar, 1951- (New York, USA Routledge, 2025)
This important book introduces the Health in All Policies (HiAP) approach to health promotion, not only detailing how policy-making at all levels can foster the right conditions for better public health but also examining the inherent challenges to such an overarching approach. Building on the author's extensive experience in health promotion planning in both regional and international contexts, the book recognizes those factors which influence public health outside of healthcare services themselves. Addressing these broader social, economic and even cultural issues, it discusses how policy-making between the public and private sectors, as well as local and national government, should be both collaborative and holistic. But the book also reflects upon the key difficulties in integrating multi-sector and multi-level approaches - both top-down and bottom-up policy-making - to create processes that further health equity and empower individuals and communities. Now at the forefront of current thinking in health promotion and health policy, this insightful overview of HiAP will be essential reading for students and researchers across the Health Sciences, specifically Public Health and Social Policy, as well as every practitioner in the field.
Keywords: Health planning; Health promotion; MEDICAL / Health Policy; MEDICAL / Public Health; HEALTH & FITNESS / Healthy Living